PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN, DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI PROPERTI PADA MASYARAKAT KECAMATAN GONDANGREJO - Rinda Yuisticia Hapsari; Muhammad Hasan Ma'ruf; Desy Nur Pratiwi (Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of financial literacy on property investment decisions, the influence of financial behaviour on property investment decisions, and the influence of income on property investment decisions. This research uses descriptive and quantitative research methods. The population in this study was 154 commercial housing investors recorded on the Sikumbang platform. And the sample obtained by calculating the Slovin formula was 61 respondents. The data obtained was collected by distributing questionnaires to respondents. The data analysis used is a validity test, reliability test, classical assumption test, descriptive analysis, multiple linear regression analysis, F test, t test, and coefficient of determination test. The result of this research show that financial literacy and income variables have a positive and significant influence on property investment decisions, and financial behaviour variable do not have a positive and significant influence on property investment decisions among the people of Gondangrejo District.